The Vaccine Against COVID-19: A Race Against Time - Hernández Fernández, Javier (Revista Mutis, 2020)
More than 16,5 million people have been infected with covid-19 worldwide, resulting in 655,300 deaths and immeasurable economic disruption. After the initial outbreak and more than 220,000 cases and 7,000 deaths in Colombia, covid-19 has widespread across 188 countries. The infection progresses daily, and cases and deaths increase mainly in the United States, Brazil, Russia, India, and South America countries such as Peru, Mexico, Chile, and Colombia.